2022
DOI: 10.1158/1538-7445.sabcs21-gs4-08
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS4-08: Comprehensive genomic profiling of patients with breast cancer identifies germline-somatic interactions mediating therapy resistance

Abstract: Background: Germline genetic alterations are established mediators of breast carcinogenesis, often giving rise to specific forms of genomic instability. BRCA1/2 pathogenic variants (PVs) are emblematic of this phenomenon through their induction of homologous recombination deficiency. While specific patterns of genomic instability may sensitize cancers to therapies such as PARP inhibitors (PARPi) or platinum chemotherapy, their implications for lineage-directed therapies such as endocrine therapy (ET) or CDK4/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
0
7
1
2
Order By: Relevance
“…DNA repair defect (DRD) gene mutations may confer resistance to CDK4/6i. Safonov et al recently reported gBRCA2 mutation in association with significantly inferior PFS (HR 2.17, 95% CI 1.46-3.22, p < 0.001) for 1st-line treatment with CDK4/6 I [47]. No significant association between PALB2 mutation and PFS with CDK4/6i was identified in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…DNA repair defect (DRD) gene mutations may confer resistance to CDK4/6i. Safonov et al recently reported gBRCA2 mutation in association with significantly inferior PFS (HR 2.17, 95% CI 1.46-3.22, p < 0.001) for 1st-line treatment with CDK4/6 I [47]. No significant association between PALB2 mutation and PFS with CDK4/6i was identified in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…Retrospective analyses showed that outcomes with CDK4/6 inhibitors may be poorer in carriers of gBRCA1/2 variants compared with wild-type patients . In cases of gBRCA2 variants, this might be due to the co-occurrence of BRCA2 loss of heterozygosity and loss of RB1, a gene located in proximity to BRCA2 on chromosome 13, in which loss is a well-known mechanism of resistance to CDK4/6 inhibitors . Furthermore, gBRCA -associated tumors are more often nonluminal compared with sporadic ER-positive tumors .…”
Section: Discussionmentioning
confidence: 99%
“…At this conference, data were presented showing that a germline mutation in BRCA2 had an unfavorable effect on the prognosis for patients treated with a CDK4/6 inhibitor. Compared to patients with the wild-type genotype, patients with a mutation had a higher risk of progression (HR = 2.32; 95% CI: 1.38 – 3.91) 28 .…”
Section: Hormone Receptor-positive Disease and Cdk4/6 Inhibitorsmentioning
confidence: 98%
“…Dort wurden Daten präsentiert, dass bei Patientinnen, die mit einem CDK4/6-Inhibitor behandelt werden, eine Keimbahnmutation in BRCA2 einen ungünstigen prognostischen Effekt hat. Verglichen mit Patientinnen mit einem Wildtyp-Genotyp hatten Patientinnen mit einer Mutation ein höheres Risiko für einen Progress (HR = 2,32; 95 %-KI: 1,38-3,91) [28].…”
Section: Msk Impactunclassified